Reducing Postharvest Loss of Stored Grains Using Plant-Based Biopesticides: A Review of Past Research Efforts - Getachew Bezabih; Neela Satheesh; Solomon Workneh Fanta; Melaku Wale; Minaleshewa Atlabachew (Advances in Agriculture)
The world population is projected to be 9.1 billion by the year 2050, and about 70% extra food will be required. One of the main challenges regarding food security is postharvest loss due to insect pests. The overall postharvest grain losses for sub-Saharan Africa could be as high as US$4 billion/year. This is around 15% of the total production of cereal crops. The use of chemical pesticides to reduce grain damage by insects over the past five decades has led to a range of environmental and human health problems. These problems forced researchers to develop alternative methods that have lower adverse effects. Alternative strategies focus on new forms of pesticides that are effective against a specific target species, have fewer residues in food, are unlikely to contaminate the environment, and have lower potential to produce resistance, are biodegradable, and are suitable for use in integrated pest management programs. Some natural plant products effectively meet these criteria and have the potential to manage insect pests of stored grains. However, the understanding of the use of botanical pesticides in storage pest management systems is limited in most parts of sub-Saharan African countries. Effective plant products are not formulated and used widely. To fill the gaps the first step is to synthesize the available information and disseminate it. This review is, therefore, a summary of the current developments and improvements of botanical pesticides in the management of stored grain pests including challenges and future issues in insect pest management.